THE CHOICE OF TOOL FOR ASSESSING THE COMPETITIVENESS OF AN INDUSTRIAL ENTERPRISE AS A MECHANISM FOR IMPROVING THE CAPACITY OF ITS INTANGIBLE ASSETS - I. Buzurnaya (Publishing House of the State University of Management, 2016)
The article considers features of development of the mechanism of increase of the potential intangible assets of industrial enterprises through the selection of the tool for assessing the competitiveness of an industrial enterprise with the purpose of monitoring the effectiveness of implemented solutions and monitor the degree of their influence on competitiveness of industrial enterprises.